1985
DOI: 10.3354/meps024083
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of an introduced mudflat community in South San Francisco Bay, California

Abstract: The benthic invertebrate community inhabiting the extensive and sedimentologically homogeneous mudflats of South San Francisco Bay has demonstrated a high degree of constancy in both species composition and relative abundance among species throughout 10 yr of observation. The community, composed predominantly of introduced species with opportunistic lifestyles, is dominated numerically by Gemma gernma, Ampelisca abdita, and Streblospio benedicti. The key to the persistent CO-occurrence of these species on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
0

Year Published

1987
1987
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(63 citation statements)
references
References 44 publications
4
59
0
Order By: Relevance
“…Nichols (1979Nichols ( , 1985 noted that natural perturbation~ easily mask possible anthropogenic effects. Nichols & Thompson (1985) could not, in 10 yr of observation of a mudflat community in the Bay, differentiate benthic community change due to other than catastrophic pollution events from natural variation.…”
Section: Discussionmentioning
confidence: 99%
“…Nichols (1979Nichols ( , 1985 noted that natural perturbation~ easily mask possible anthropogenic effects. Nichols & Thompson (1985) could not, in 10 yr of observation of a mudflat community in the Bay, differentiate benthic community change due to other than catastrophic pollution events from natural variation.…”
Section: Discussionmentioning
confidence: 99%
“…(Chesney & Tenore 1985a, Gremare et al 1989), leading to varying population abundance patterns over the long-term (e.g. Nichols & Thompson 1985).…”
Section: Discussionmentioning
confidence: 99%
“…Each plot was sampled twice, 2 wk apart, in February 2000. Previous studies in soft-sediments (Nichols & Thompson 1985, Livingston 1987, Morrisey et al 1992b) and in mangroves (Underwood & Chapman 1999) have shown large variability in the abundance and composition of fauna over periods of days, weeks or months. Therefore, the replicate cores were sampled to test the hypothesis that the patterns of abundance were consistent over short periods of time and to identify the scale of any spatio-temporal interactions.…”
Section: Methodsmentioning
confidence: 99%